Employee creativity deterrence by abusive supervision through the lens (mediation) of employee silence - Sufyan Zia; Kaleem Ahmed (Cogent Business & Management, 2024)
Based on the interactionist perspective of organizational creativity, conservation of resource theory and social exchange theory, this study finds out the contextual factors from the social context of the organizations that affect the creativity of an employee. Data from the 443 engineers of software houses in Pakistan is collected through questionnaires. SPSS version 25 is used for demographics, internal reliability and mediation through Hayes macro process. AMOS26 is used for internal consistency, convergent validity and discriminant validity. Hayes macro process model 4 is used for mediation analysis. Findings have confirmed that abusive supervision is one of the major reasons behind the decrease in employee creativity. Employee silence partially mediates their relationship as the relationship between abusive supervision and employee creativity still remains significant. The mediating role of employee silence in the relationship between abusive supervision and employee creativity is an important novelty of this study. Several future directions about partial mediation, measuring scales and malevolent creativity are discussed in the future directions section of the study.Creativity is an important tool for organizations to stay competitive in this globalized ever changing business environment. It is important to figure out the factors influencing it. Abusive supervision is among one of those factors. This study finds out the relationship between abusive supervision and employee creativity. Another important aspect is about finding the path/mechanism through which creativity of an employee is affected.This study is important for organizations directly connected with creativity. A more in depth review of their supervision systems can help to increase the creativity of their employees and hence can improve the performance of those organizations. Appropriate measures to overcome such issues are also suggested in practical implications section of this study.
Keywords: 650; Abusive supervision; employee creativity; employee silence; social exchange theory; innovation; hayes macro process; conservation of resource theory